Investigation of the equilibrium and non–equilibrium models of heat and moisture transport in a wet porous building material - Seredyński Miroslaw; Wasik Michał; Łapka Piotr; Furmański Piotr; Cieślikiewicz Łukasz; Pietrak Karol; Kubiś Michał; Wiśniewski Tomasz S.; Jaworski Maciej (E3S Web of Conferences, 2019)
In the paper the equilibrium and non-equilibrium models of moisture transport across the wet building material are proposed and compared. The equilibrium condition between gaseous and liquid moisture phases in the first model is relaxed in the second one, where evaporation and condensation are driven by the difference between the actual moisture partial pressure and its saturation value. In both models moisture is assumed in the gaseous phase as well as continuous (funicular) and discontinuous (pendular) liquid phase. Moreover, the transport of moisture is tightly coupled with heat transfer, which is treated as the fully equilibrium process in both models. The proposed models are verified with numericalresults available in literature, namely with temporal variation of temperature in selected location in the building material. Additionally, predicted with both models temporal changes of the moisture content in three selected points and the total moisture content are compared. Both models produced similar results.